WHY “HARVARD UNIVERSITY: NEEDS LEAD THE NEXT LINGUISTIC REVOLUTION - Mahmudjon Kuchkarov (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Introduction: The Problem No One Is Solving… For decades, modern linguistics has revolved around abstract theories divorced from reality — from Saussure’s arbitrary signs to Chomsky’s generative grammar. While these frameworks advanced formal analysis, they failed to answer the fundamental question: Where does human language actually come from? The answer — long ignored — is not in grammar or syntax. It is in the body, the senses, and the primordial interactions between humans and their environment. This is the foundation of the “Odam Tili” Theory, developed over 21 years of independent empirical research by Dr. Kuchkarov in the multilingual ecosystem of New York City.